Bio-activities of the methanol extracts from some species belonging to the genus Polygonum in Lam Dong province - Dieu Thuan, Nguyen Thi; Toan Phan, Nguyen Huu; Duc, Hoang Thi; Trung, Nguyen Dinh (Academia Journal of Biology, 2012)
The methanol extracts from the aerial parts of eight species (Polygonum odoratum Lour., P. pesicaria L., P. chinensis L., P. perfoliatum L., P. alatum Buch.-Ham. ex D. Don, P. strigosum R. Br., P. orientale L., P. hydropiper L.) collected in Lam Dong province were submitted to bio-tests in order to evaluate the antibacterial, antioxidant and cytotoxic effects. All of these extracts had antimicrobial activities, especially P. strigosum R. Br. could resist to E. coli, S. aureus, F. oxysporum, A. niger and S. cerevisiae; P. orientale L. could resist to S. aureus, B. subtillis, F. oxysporum and A. niger; P. hydropiper could resist E. coli, S. aureus, B. subtillis, F. oxysporum, A. niger and S. cerevisiae. As far as DPPH test, the MeOH extracts from P. chinensis L., P. perfoliatum L. and P. alatum Buch.-Ham. ex D. Don were found to be the most active extracts. The MeOH extracts from these eight species had antioxydant and antimicrobial activities, therefore they had been used to cure the skin desease in the traditional medicine.